Transcriptome analysis of megalurothrips usitatus (Bagnall) identifies olfactory genes with ligands binding characteristics of MusiOBP1 and MusiCSP1 - Li, Zhaoyang; Chen, Weiyi; Wang, Xiaoshuang; Sang, Wen; Pan, Huipeng; Ali, Shaukat; Tang, Liangde; Wu, Jianhui (Frontiers in Physiology, 2022)
The olfactory system is an important component of insect behavior and is vital for survival and reproduction. However, the genomic characterization and molecular basis of the olfactory response of Megalurothrips usitatus remain relatively unknown. RNA sequencing-built developmental transcriptomes of nymphs, pupae, and adult M. usitatus were examined in order to establish the sequence-based background of M. usitatus olfactory responses. A total of 56,669 unigenes were annotated using GO, NR, Pfam, eggNOG, SwissProt, and KEGG. The number of differentially expressed genes between pupae and nymphs, males and nymphs, and females and nymphs were 10,498, 9,235, and 10,964, respectively. One odorant-binding protein (MusiOBP1) and one chemosensory protein (MusiCSP1) were selected from the transcriptome, and their full-length sequences were obtained using RACE PCR. The relative expression of MusiOBP1 was the highest in primordial females, whereas the relative expression of MusiCSP1 was the highest in primordial pupae. The strongest binding ability to the odor-binding protein MusiOBP1 was observed for β-citronellol. 3-Hydroxy-2-methyl-4-pyrone showed the strongest binding affinity to MusiCSP1. Our analysis suggests that MusiOBP1 and MusiCSP1 may play significant roles in mediating M. usitatus host recognition. This research will improve our knowledge of odorant-binding proteins and chemosensory proteins, which will in turn improve our understanding of insect olfactory systems.